Influence of Local Lattice Distortion on Elastic Properties of Hexagonal Close‐Packed TiZrHf and TiZrHfSc Refractory Alloys. Issue 7 (6th May 2021) - Meng, Hong; Duan, Jia-Ming; Chen, Xiao-Tao; Jiang, Shan; Shao, Lin; Tang, Bi-Yu
Abstract : The unique mechanical properties and local lattice distortion (LLD) for hexagonal close‐packed (HCP) multiple principal element alloys (MPEAs) are very rarely studied so far. Employing density functional theory calculation based on special quasirandom structure, this work studies the influences of LLD on elastic properties for both novel hexagonal TiZrHf(Sc) MPEAs. Compared to the pristine structures, the lattice stability of distorted random structures is improved evidently. Moreover, LLD obviously lessens the shear elastic properties, which may be an ubiquitous phenomenon irrespective of the lattice types of MPEAs. These results also uncover the apparent improvement in malleable behavior and shear anisotropy for HCP MPEAs. So, the influence of LLD on elastic properties for HCP MPEAs is profound. The degree of LLD is further studied via the standard deviation of near‐neighbor (NN) and next NN bond length distributions as an effective indicator of LLD. More significant distortion uncovered in TiZrHf alloy corresponds consistently to the stronger effects of LLD in TiZrHf alloy. Bader's charge and charge density distribution also demonstrate the underlying impact on LLD for both HCP MPEAs, so electronic nature is a significant factor for LLD. The present study provides guideline for designing mechanical properties of TiZrHf‐based HCP MPEAs engineering materials. Abstract : The influence of local lattice distortion (LLD) on elastic properties of hexagonal close‐packed (HCP) refractory multiple principal element alloys (MPEAs) TiZrHf and TiZrHfSc has been studied systematically using the first‐principles method. The present study evidently indicates that LLD lessens the shear elastic properties and improves the malleable behavior and shear anisotropy of both TiZrHf(Sc) HCP MPEAs.